Tackling a-Alkyl imines with 3d metal catalysis: highly enantioselective iron-catalyzed synthesis of α-chiral amines - Blasius, Clemens K.; Heinrich, Niklas; Vasilenko, Vladislav; Gade, Lutz H. (Angewandte Chemie, 2020)
A readily activated iron alkyl precatalyst effectively catalyzes the highly enantioselective hydroboration of N-alkyl imines. Employing a chiral bis(oxazolinylmethylidene)isoindoline pincer ligand, the asymmetric reduction of various acyclic N-alkyl imines provided the corresponding α-chiral amines in excellent yields and with up to >99 % ee. The applicability of this base metal catalytic system was further demonstrated with the synthesis of the pharmaceuticals Fendiline and Tecalcet.